(untitled) (CIPEEX, 2022)
IT IS UNDERSTOOD THAT INCLUSION IS BASICALLY ACCEPTING ANY PERSON IN DIFFERENT SITUATIONS REGARDLESS OF THEIRPECULIARITIES AND DIFFERENCES, WHICH GENERATES GREAT OPPORTUNITIES FOR ALL IN DIFFERENT CIRCUMSTANCES, WHETHER INJOBS OR EDUCATION. HOWEVER, INCLUSION IS NOT WITNESSED IN VARIOUS SOCIAL SPHERES, GIVEN THAT LARGE BARRIERS ARESTILL IMPOSED ON PEOPLE WITH SPECIAL NEEDS, SUCH AS A LIBRARY, WHERE THE VISUALLY IMPAIRED IS NOT CONTEMFACEDWITH A BRAILLE BOOK, THUS LOSING THEIR OPPORTUNITY TO ACCESS INFORMATION. THEREFORE, THE PRESENT STUDY AIMED TOSHOW THE LIMITATIONS THAT A DEFICIENT PERSON EXPERIENCES IN THE CURRENT SOCIETY BY ANOTHER POINT OF VIEW, NOTEVIDENCING THE DIFFICULTIES FACED BY THESE PEOPLE, BUT RATHER STIMULATING THE REFLECTION OF ALL, MAKING THEY PUTTHEMSELVES IN PLACE OF THESE INDIVIDUALS. FOR THIS, A REVERSAL OF WORLDS WAS PROPOSED, THAT IS, AN EXCHANGE OFEXPERIENCES, WHERE THE NORMAL WAS CONSIDERED DIFFERENT, SHOWING THE DIFFICULTIES IN A WORLD ADAPTED ONLY FOR THEHANDICAPPED. THUS, SEVERAL DRAWINGS WERE PRODUCED AND EXPOSED IN DIFFERENT CONTEXTS, SUCH AS A PARKING LOT,WHICH IN ITS ENTIRETY MOST OF THE VACANCIES ARE DESTINED TO PEOPLE WITH SPECIAL NEEDS, A FACULTY THAT ONLYCOMMUNICATES IN THE LANGUAGE OF SIGNS, A LIBRARY THAT HAS ONLY BRAILLE BOOKS, A TV SHOW BROADCAST ONLY INLIBRAS AND ALSO ESTABLISHMENTS THAT DO NOT HAVE CHAIRS, ONLY TABLES, FOR WHEELCHAIR USERS TO SETTLE. THE VARIOUSSITUATIONS WERE DRAWN AND COLOURED WITH CRAYONS AND GLUED TO EVA. IN CARDBOARDS, WORDS WERE MADE IN BRAILLEABOUT LOVE, RESPECT, EQUALITY, ACCESSIBILITY, AMONG OTHERS. THESE WORDS AND THEIR MEANINGS WERE INTERTWINEDWITH SATIN RIBBONS WITH THE ILLUSTRATIONS, ALONG WITH THEIR RESPECTIVE EXPLANATORY PHRASES. ALL THESE ITEMSCOMPRISED A KIND OF CLOTHESLINE TO BE EXPOSED TO THE PUBLIC. AS A RESULT, THE PRESENT WORK WAS PRESENTED AS ONEOF THE ATTRACTIONS EXHIBITED AT THE V CULTURAL SHOW OF DENTISTRY COURSE OF THE UNIVERSITY CENTER OF ANÁPOLIS(UNIEVANGLICA) WHERE IT COULD BE CONTEMED BY ACADEMICS AND PROFESSORS OF THE INSTITUTION AT THE SAME TIME INTHAT ONE OF THE DEVELOPERS OF THE IDEA EXPLAINED AND ANSWERED DOUBTS ABOUT THE SUBJECT ADDRESSED. IT WASCONCLUDED, THEREFORE, THAT THE PRESENT WORK AROUSED THE CURIOSITY AND REFLECTION OF THE SPECTATORS, MAKING THEMRETHINK THEIR PRECONCEPTIONS AND THE DIFFICULTIES EXPERIENCED BY THE HANDICAPPED DAILY. BESIDES CONTRIBUTING TOTHE DEVELOPMENT OF A HUMANISTIC PROFILE BY THE ALREADY PROFESSIONALS AND FUTURE PROFESSIONALS OF DENTISTRY.KEYWORDS: INCLUSION. DISABLED. LIMITATIONS.